1988
DOI: 10.1021/bi00419a041
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of band 3 mobilities in erythrocyte ghost membranes by protein association and cytoskeletal meshwork

Abstract: Rotational diffusion of erythrocyte anion channel protein band 3 was measured in ghost membranes by observing time-resolved phosphorescence anisotropy decays of eosinyl-5-maleimide covalently attached to the protein. Experiments were carried out under conditions similar to those employed by Tsuji and Ohnishi (1986) for translational diffusion measurement of band 3 [(1986) Biochemistry 25, 6133-6139] to allow direct comparison of rotational and translational diffusion of band 3. Detailed analysis of diffusive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
95
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 32 publications
15
95
1
Order By: Relevance
“…1a). Indeed, FRAP measurements on erythrocytes membrane (see also [19]) suggested that membrane proteins are confined by steric interaction of their cytoplasmic part with spectrin cytoskeleton. This model was reinforced by electron microscopy imaging of the sub-membrane region that showed unambiguously that spectrin forms a meshgrid tightly attached to the membrane via transmembrane band-3 proteins [20].…”
Section: The Cytoskeleton Meshwork Is a Barrier To Diffusionmentioning
confidence: 99%
“…1a). Indeed, FRAP measurements on erythrocytes membrane (see also [19]) suggested that membrane proteins are confined by steric interaction of their cytoplasmic part with spectrin cytoskeleton. This model was reinforced by electron microscopy imaging of the sub-membrane region that showed unambiguously that spectrin forms a meshgrid tightly attached to the membrane via transmembrane band-3 proteins [20].…”
Section: The Cytoskeleton Meshwork Is a Barrier To Diffusionmentioning
confidence: 99%
“…Abundant evidence implicates the RBC membrane skeleton in controlling band 3 lateral mobility. Disruption of spectrin-ankyrin and ankyrin-band 3 linkages causes band 3 mobility to increase (21)(22)(23)(24), as does treatment with proteases to remove the cytoplasmic domain of band 3 (25,26) or treatment with ATP or 2,3-DPG (27) at levels that are sufficient to destabilize isolated RBC membrane skeletons (28) Band 3 rotational mobility has been studied in normal RBC ghosts (26,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), abnormal RBC ghosts (45,46), and intact RBCs (19,31,37).2 Rapidly rotating, slowly rotating, and rotationally immobile forms of band 3 appear to coexist in the membrane. At 37°C in normal RBC membranes, 20-25% of band 3 molecules rotate with correlation times (r) < 250 Ms, 50-75% rotate with r 1-3 ms, and 5-25% are rotationally immobile on the time scale of the experiment (19,37,40 About half of the rapidly rotating band 3 molecules may rotate with correlation times of 25-30 ,ts; this population could represent band 3 dimers rotating free of constraints other than the viscosity of the lipid bilayer (37).…”
Section: Introductionmentioning
confidence: 99%
“…At 37°C in normal RBC membranes, 20-25% of band 3 molecules rotate with correlation times (r) < 250 Ms, 50-75% rotate with r 1-3 ms, and 5-25% are rotationally immobile on the time scale of the experiment (19,37,40 About half of the rapidly rotating band 3 molecules may rotate with correlation times of 25-30 ,ts; this population could represent band 3 dimers rotating free of constraints other than the viscosity of the lipid bilayer (37). A number of experiments on RBC ghost membranes suggest that band 3 rotational mobility, like band 3 lateral mobility, is controlled by the RBC membrane skeleton (26,36,37,43). In addition, SAO RBCs exhibit a very large fraction of rotationally immobile band 3 (30,31,46).…”
Section: Introductionmentioning
confidence: 99%
“…Glycophorin A, present in -5 x 105 copies per cell (5), is the major sialoglycoprotein. The membrane skeleton determines RBC stability, deformability, and shape (6-9) and appears to regulate lateral and rotational mobility of band 3 and glycophorin A in the plane ofthe membrane (10)(11)(12)(13)(14)(15)(16)(17)(18). The major skeletal protein, spectrin, is attached to the overlying bilayer through interactions involving: ankyrin, which links spectrin to a portion ( 10-15%) of band 3; protein 4.1, which links spectrin to glycophorin C and possibly to glycophorin A and band 3; and, possibly, inner leaflet aminophospholipids, including phosphatidylserine and phosphatidylethanolamine (2).…”
Section: Introductionmentioning
confidence: 99%